Decoding signaling mechanisms: unraveling the targets of guanylate cyclase agonists in cardiovascular and digestive diseases - Yin, Qinan; Zheng, Xingyue; Song, Yujie; Wu, Liuyun; Li, Lian; Tong, Rongsheng; Han, Lizhu; Bian, Yuan (Frontiers in Pharmacology, 2023)
Soluble guanylate cyclase agonists and guanylate cyclase C agonists are two popular drugs for diseases of the cardiovascular system and digestive systems. The common denominator in these conditions is the potential therapeutic target of guanylate cyclase. Thanks to in-depth explorations of their underlying signaling mechanisms, the targets of these drugs are becoming clearer. This review explains the recent research progress regarding potential drugs in this class by introducing representative drugs and current findings on them.